Effectiveness of Flavonoids as Osteoporosis Prevention in Menopausal Women: A Systematic Review of Randomized Controlled Trials - Rulitasari; Ariq Fadhil Athalah; Fida Nabila Purnomo; Muhammad Azri Ismail; Raihan Ilyasa Rizkullah (Asian Journal of Health Research, 2024)
Introduction: Osteoporosis impacts over 200 million people globally, especially those aged 70 and above, with a prevalence of 18.3% worldwide and 10.3% in Indonesia. Diagnosis is based on WHO criteria of -2.5 SD or lower BMD, often caused by aging or medications like glucocorticoids. Treatment includes lifestyle changes, supplements, and drugs like HRT and bisphosphonates despite HRT's risks. Flavonoids from plants have shown potential in bone health through RCTs, explored in this review via serum biomarkers. This systematic review seeks to investigate the potential effectiveness of flavonoid in managing osteoporosis in patients by analyzing serum bone biomarkers Materials/Methods: A literature search across six databases assessed changes in BMD and other serum bone biomarkers in studies using flavonoid interventions like extracts, genistein, resveratrol, and isolated soy protein. Study quality was evaluated with the Cochrane Risk of Bias Tool 2, and 12 articles were included in the review. Results: Twelve studies revealed that the intervention group experienced significantly greater mean changes in BMD and BAP values compared to the control group following flavonoid treatment (P<0.05). The studies also showed that flavonoid notably increased several bone formation markers, such as osteocalcin, and reduced bone resorption markers, including DPD, TRACP-5b, and bCTX. Conclusion: Flavonoid intervention has been shown to effectively enhance bone mineral density and improve serum bone biomarkers. This study highlights the potential of flavonoids as a treatment option for patients with osteoporosis.